2018
DOI: 10.1093/cercor/bhy089
|View full text |Cite
|
Sign up to set email alerts
|

RIPK3/MLKL-Mediated Neuronal Necroptosis Modulates the M1/M2 Polarization of Microglia/Macrophages in the Ischemic Cortex

Abstract: Cell death and subsequent inflammation are 2 key pathological changes occurring in cerebral ischemia. Active microglia/macrophages play a double-edged role depending on the balance of their M1/M2 phenotypes. Necrosis is the predominant type of cell death following ischemia. However, how necrotic cells modulate the M1/M2 polarization of microglia/macrophages remains poorly investigated. Here, we reported that ischemia induces a rapid RIPK3/MLKL-mediated neuron-dominated necroptosis, a type of programmed necrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 50 publications
(58 reference statements)
5
70
0
1
Order By: Relevance
“…65 Manipulation of this microglial/macrophage polarization is a neuroprotective strategy after stroke. 66 In a recent publication, Yang et al 67 demonstrated a link between necroptosis and the M1/M2 polarization of the ischemic cortex of the brain. The authors discovered that without RIPK3 or MLKL, both microglia and macrophages polarized to the M2 phenotype in the ischemic cortex.…”
Section: Strokementioning
confidence: 99%
“…65 Manipulation of this microglial/macrophage polarization is a neuroprotective strategy after stroke. 66 In a recent publication, Yang et al 67 demonstrated a link between necroptosis and the M1/M2 polarization of the ischemic cortex of the brain. The authors discovered that without RIPK3 or MLKL, both microglia and macrophages polarized to the M2 phenotype in the ischemic cortex.…”
Section: Strokementioning
confidence: 99%
“…Focal cortical ischemia was induced by photothrombosis of the cortical microvessels as described previously (Yu et al, 2015;Yang et al, 2018). Rose bengal (Sigma, Cat# 330000) was injected intraperitoneally (ip.)…”
Section: Photochemical Ischemia and Mouse Treatmentmentioning
confidence: 99%
“…Increasing evidence suggests that microglia may be important cellular targets in ischemic stroke (Ma, Wang, Wang, & Yang, ; Rahimian et al, ). Intervening in microglia‐mediated inflammation has been considered as a prime strategy for the development of new ischemic stroke therapies (Lambertsen, Finsen, & Clausen, ; Qin et al, , ; Yang et al, ; Yew et al, ).…”
Section: Introductionmentioning
confidence: 99%